Determinants of partial and adequate maternal health services utilization in Nigeria: analysis of cross-sectional survey - Sulaimon T. Adedokun; Olalekan A. Uthman; Luqman A. Bisiriyu (BMC, 2023)
Abstract Background Access to health services during pregnancy, childbirth and the period after birth provides a substantial opportunity to limit cases of maternal mortality. In sub-Saharan Africa, the proportions of women who utilize health services remain below 70%. This study examined the factors associated with partial and adequate maternal health services utilization in Nigeria. Methods This paper used data from 2018 Nigeria Demographic and Health Survey (DHS) comprising 21,792 women aged 15-49 years who had given births within five years of the survey. The study focused on antenatal care attendance, place of birth and postnatal care using a combined model. Multinomial logistic regression was applied in the analysis. Results About 74% of the women attended antenatal care, 41% gave birth in health facilities and 21% attended postnatal care. While 68% of the women partially utilized health services, 11% adequately utilized the services. The odds of partially and adequately utilizing health services increased for ever married women, women with secondary or higher education, from richest households, living in urban area, having no problem either getting permission to visit health facility or reaching health facility. Conclusions This study has revealed the factors associated with partial and adequate utilization of maternal health services in Nigeria. Such factors include education, household wealth, marital status, employment status, residence, region, media exposure, getting permission to use health service, unwillingness to visit health facility without being accompanied and distance to health facility. Efforts aimed at improving maternal health services utilization should place emphasis on these factors.